Biological characterisation of a recombinant pseudorabies virus - Alvarez, E.=700 1 Prieto, C.; Martinez Lobo, F.J.; Castro, J.M.
(En, Es)
Ilus., 34 ref.
Keywords: LECHON; INMUNIZACION; PROTECCION DE LA SALUD; SEGURIDAD; VACUNAS; ENFERMEDAD DE AUJESZKY; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH